Drivers of and barriers to eco-innovation: a case study. (2016) - Hojnik, Jana; Ruzzier, Mitja
This study seeks to elucidate the drivers of and barriers to eco-innovation deployment. In order to obtain greater insight into the motives for and hindrances to eco-innovation deployment, we employ a case study approach, based on interviews of five Slovenian companies active in eco-innovation. The main insights of this study are threefold. First, companies seem to be influenced by both internal and external drivers in implementing eco-innovation. Among the internal drivers, the most emphasis has been placed on environmental concerns and cost reduction, while the most important external drivers are customer pressure, competition and regulatory pressure. Second, barriers to eco-innovation also derive from external and internal pressures. Costs (upfront investment for eco-innovation implementation) prevail within the internal barriers, while legislation seems to be the most commonly experienced external barrier. Finally, the outcomes of eco-innovation that companies most often expect are reduction in costs and compliance with legislation, which is coherent with reported outcomes.